Effects of Employee Engagement Toperfomance (Case Study: Insurance Company in Indonesia) - Yona Melia; Nidya Dudija (AIBPM Publisher, 2019)
One factor that affects performance is employee engagement. Based on the data, uneven performance on each type of work and the percentage of employee attendance increased for the last three years in a row. This study aims to determine the effect of employee engagement on performance and is a descriptive and quantitative statistic with the effect of analysis using path analysis. The study was conducted using primary data based on the distribution of questionnaires consisting of 28 statements using 51 employees as a sample. The results showed that the variable on employee engagement had a significant influence on performance with the effect of vigor of -7.12%, dedication of 13.91%, absorption of 35.86 and simultaneously 42.65%.